Lifelong Effects of Thermal Challenges During Development in Birds and Mammals - Nord, Andreas; Giroud, Sylvain (Frontiers in Physiology, 2020)
Before they develop competent endothermy, mammals and birds are sensitive to fluctuating temperature. It follows that early life thermal environment can trigger changes to the ontogeny of thermoregulatory control. At the ecological level, we have incomplete knowledge of how such responses affect temperature tolerance later in life. In some cases, changes to pre- and postnatal temperature prime an organism’s capacity to meet a corresponding thermal environment in adulthood. However, in other cases, developmental temperature seems to constrain temperature tolerance later in life. The timing, duration, and severity of a thermal challenge will determine whether its impact is ameliorating or constraining. However, the effects influencing the transition between these states remain poorly understood, particularly in mammals and during the postnatal period. As climate change is predicted to bring more frequent spells of extreme temperature, it is relevant to ask under which circumstances developmental thermal conditions predispose or constrain animals’ capacity to deal with temperature variation. Increasingly stochastic weather also implies increasingly decoupled early- and late-life thermal environments. Hence, there is a pressing need to understand better how developmental temperature impacts thermoregulatory responses to matched and mismatched thermal challenges in subsequent life stages. Here, we summarize studies on how the thermal environment before, and shortly after, birth affects the ontogeny of thermoregulation in birds and mammals, and outline how this might carry over to temperature tolerance in adulthood. We also identify key points that need addressing to understand how effects of temperature variation during development may facilitate or constrain thermal adaptation over a lifetime.